The Development of the Papica Reading Smart Board Media in Improving Basic Literacy of Children in The Early Childhood Education Curriculum - Heriana, Heriana; Herlina, Herlina; Syamsuardi, Syamsuardi; Rusmayadi, Rusmayadi (Pusat Penerbitan Universitas (P2U) Unisba, 2024)
This research is an R&D research which aims (1) to find out the need for the use of reading smart board learning media (e-papica) in implementing the independent curriculum to improve basic literacy in early childhood (2) To find out the development of reading smart board learning media (e-papica) in improving basic literacy in early childhood (3) To find out the validity, practicality and effectiveness of reading smart board learning media (e-papica) in improving basic literacy skills in children. This research design uses a 4-D model. Data collection techniques in this research were observation and questionnaires. The subjects in this research consisted of 4 teachers and 30 students. The results of the research show that: (1) an overview of the need for developing reading smart board learning media (e-papica) in improving children's basic literacy, is really needed by teachers because reading smart board learning media (e-papica) is considered very practical in improving basic literacy skills in children, 2) The development plan for reading smart board (e-papica) is designed, namely: Media and guidebooks for using the media, and 3) the level of validity of reading smart board learning media (e-papica) is obtained in the valid category, and the level of practicality obtained with very practical criteria. Meanwhile, in the effectiveness test, the media evaluation sheet was found to be in the very effective category. and analysis of the children's data obtained shows that H1 is accepted and H0 is rejected, so it is said that there is an influence of smart reading board media (e-papica) on children's basic literacy.